Radioactive contamination in Iraq and its impact on birth defects for the period (2004-2013) (Journal of the College of Education for Women, 2019)
In the present time, radioactive contamination is considered one of the most dangerous types of environmental pollution. It usually takes place because of a leakage of radioactive materials to one of the environment natural components, such as, water, air, and soil. Iraq is considered one of the most contaminated environments in the world; this is closely associated with the wars Iraq had suffered from; especially, in 1991 and 2003. Considering the importance of the radioactive contamination and its different health impacts on the population, the current paper is interested in studying this type of environmental contamination and its impact on the birth defects depending on the data available in the annual reports issued by the Iraqi ministry of health.Several conclusions were drawn from the current work, among them, is that Iraq is obviously still suffering from the radioactive contamination leftover by wars and that the cities located in the middle and south of Iraq are the most affected ones by this type of contamination because it lies within the wars’ map and it contains 75% of the total population.According to the registered birth defects’ ratios in the period between 2004 and 2013, Baghdad ranked the first with a concentration ratio of 22.3% from the total birth defects in Iraq, followed by Nineveh Province with a ratio of 20.9%, then Basrah and Anbar provinces with a ratio of 9.7% and 9.0%, respectively. However, the minimum ratio belonged to Al-Muthanna province which registered only 1.2% berth defects’ ratio.